A Case of Diprosopus: Perinatal Counseling and Management - Kimberly M. Thornton; Timothy Bennett; Vivekanand Singh; Neil Mardis; Jennifer Linebarger; Howard Kilbride; Kristin Voos (Hindawi Limited, 2014)
Diprosopus is a rare congenital malformation associated with high mortality. Here, we describe a patient with diprosopus, multiple life-threatening anomalies, and genetic mutations. Prenatal diagnosis and counseling made a beneficial impact on the family and medical providers in the care of this case.